From the Territory of Recovery to Sustainable Development: a Methodological Concept of Effective Socio-economic Development of Ukraine after the War Development - Martynovych, Nataly; Yemchenko, Iryna; Kulinich, Tetiana (Problemy Ekorozwoju, 2023)
The article is devoted to substantiating theoretical and methodological foundations and developing practical approaches to effective socio-economic development of Ukraine after the war, based on the concept of sustainable development. The study substantiates the need to build a fundamentally new economic model of post-war development of the territories of Ukraine, based on the rejection of raw material exports. It is proved that sustainable development forms the conceptual basis in the post-war economy of Ukraine. The concept of conversion of territories is proposed and the reasons are given for the need for their distribution according to the added value and quality of life of the population. The practical value of the matrix method in the division of territories according to their functional purpose is substantiated. Sets of estimated indicators of economic and social results and effectiveness of Ukraine’s recovery after the war for territories to be restored and territories of sustainable development have been developed. The procedure for assessing the effectiveness of socio-economic development of Ukraine after the war is structured. The expediency of interpreting an integral indicator based on the generalized Harrington desirability function is justified.